CONSERVATIVE VERSUS OPERATIVE TREATMENT OF CLINICALLY SUSPECTED UNCOMPLICATED ACUTE APPENDICITIS - Ahmad, Rzgar Muhedin (Journal of Sulaimani Medical College, 2024)
Background Acute appendicitis is one of the most frequent causes of an acute abdomen. There is an important controversy concerning the management of acute, uncomplicated appendicitis by surgery and nonsurgical means. Objectives To evaluate the results of conservative treatment in cases of clinically uncomplicated acute appendicitis, starting with antibiotics as an initial step. Patients and Methods A 2-year prospective study, from February 2021 to January 31, 2023, was conducted in Sulaimani Teaching Hospital in Sulaimani Governorate. Patients who presented with acute appendicitis within 72 hours of the onset of the symptoms and had an Alvarado score of ≥5 or more were included. The patients received therapeutic doses of broad-spectrum antibiotics in addition to symptomatic treatment. There was a follow-up period of six months. Results Of the 54 patients enrolled in the study, the mean age was 34.4 years; 32 (60%) were female and 22 (40%) were male. Thirteen patients (24.4%) had unsuccessful conservative treatment, compared to 41 (75.6%) who were successful. There was no recorded mortality in this research. The complications that developed in patients who did not react well to conservative treatment Eight patients with acute suppurative appendicitis—one with a perforated appendix, two with an appendicular abscess, and two with an appendicular mass—were among the surgical patients. Conclusion The majority of cases of uncomplicated acute appendicitis presented with a first attack can be successfully treated conservatively. On the other hand, conservative treatment needs good communication, vigilant observation, and frequent examination to detect failure that requires rapid surgical intervention.
Keywords: Acute appendicitis; antibiotics; conservative treatment; Alvarado score; uncomplicatedappendicitis